Degradable nanogels as a nanoreactor for growing silica colloids - Li, Yong-Yong (Langmuir : the ACS journal of surfaces and colloids, 2009)
Degradable nanogels with cleavable disulfide bonds were designed and used as a catalytic template, providing an alkali microenvironment. Well-defined hybrid silica colloids could be obtained by hydrolyzing tetraethyl orthosilicate (TEOS) in the nanogels. The size of silica colloids was found to be dependent on the size of the nanogels. After the removal of nanogels through reduction with 1,4-dithiothreitol (DTT), mesoporous silica colloids with a rough surface were obtained. The mesoporous structure of the colloids after reduction was characterized by transmission electron microscopy (TEM), surface area analysis, and X-ray diffraction (XRD). This work also provides an effective route for the preparation of mesoporous silica nanostructures, which may find wide applications as catalyst templates and drug carriers